Third Five year Plan Maharashtra State (1961-62 to 1965-66) - Planning Commission (Planning Commission, 1960)
A summary of the financial outlay proposed under the Third Five-Year Plan of Maharashtra is given in Annexure I. the total outlay proposed is Rs. 497’39 crores. The total outlay recommended by the various Study Groups appointed by the Government of Bombay in December 1958 was very much larger. While they had been asked to take note of the limitation of resources, their approach evidently was based essentially on the principle that what was physically practicable in the sphere of economic development and what was the minimum necessary in the matter of social services should be made financially practicable.
Government of Maharashtra